Pathways by which Maternal Factors are Associated With Youth Spina Bifida-Related Responsibility. (26th April 2020) - Driscoll, Colleen F Bechtel; Ohanian, Diana M; Ridosh, Monique M; Stern, Alexa; Wartman, Elicia C; Starnes, Meredith; Holmbeck, Grayson N
Abstract: Objective: Achieving condition-related autonomy is an important developmental milestone for youth with spina bifida (SB). However, the transfer of condition-related responsibility to these youth can be delayed due to parent factors. This study aimed to investigate two potential pathways by which maternal factors may be associated with condition-related responsibility among youth with SB: (a) Maternal adjustment → perception of child vulnerability (PPCV) → youth condition-related responsibility; and (b) Maternal PPCV → overprotection → youth condition-related responsibility. Methods: Participating youth with SB ( N = 140; M age =11.4 years, range = 8–15 years) were recruited as part of a longitudinal study; data from three time points (each spaced 2 years apart) from the larger study were used. Mothers reported on personal adjustment factors, PPCV, and overprotection. An observational measure of overprotection was also included. Mothers, fathers, and youth with SB reported on youths' degree of responsibility for condition-related tasks. Analyses included age, lesion level, IQ, and the dependent variables at the prior wave as covariates. Results: Bootstrapped mediation analyses revealed that PPCV significantly mediated the relationship between maternal distress and youth responsibility for medical tasks such that higher levels of distress at Time 1 predicted higher levels of PPCV at Time 2 and lower youth medical responsibility at Time 3. Furthermore, self-reported maternal overprotection significantly mediated the relationship between maternal PPCV and youth responsibility for medical tasks. Conclusions: Maternal personal distress, PPCV, and self-reported overprotection are interrelated and affect youth's condition-related responsibility. Interventions for mothers of youth with SB that target these factors may improve both maternal and youth outcomes.